Revision der westpaläarktischen Anthonomini (Coleoptera: Curculionidae). - Dieckmann, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1968)
According to this revision the westpalaearctic Anthonomini include six genera, 51 species and one subspecies. Two species (Anthonomus germanicus, Bradybatus grandoides) and one subspecies (Anthonomus chevrolati ssp. connexus) are new for science. The detailed part of this paper presents each species with the discussion of types and synonymy and with morphology, biology and geographical distribution. Contributions to the biology of some centraleuropean species are given.Nomenclatural Actscurtus Faust, 1882 (Anthonomus), syn. n. of Anthonomus (Anthonomus) kirschi Desbrochers, 1868cyprius Marshall, 1925 (Anthonomus), syn. n. of Anthonomus (Persexarthus) baudueri Desbrochers, 1875faillae Desbrochers, 1892 (Anthonomus), syn. n. of Anthonomus (Anthonomus) stierlini Desbrochers, 1869gentilis Faust, 1891 (Anthonomus), syn. n. of Anthonomus (Paranthonomus) rubripes Gyllenhal, 1836multifasciatus Pic, 1926 (Anthonomus), syn. n. of Anthonomus (Anthonomus) amygdali Hustache, 1930roberti Wencker, 1858 (Anthonomus), Lectotype; syn. n. of Anthonomus spilotus Redtenbacher, 1849rosarum Daniel, 1898 (Anthonomus), syn. n. of Anthonomus (Anthonomus) terreus Gyllenhal, 1836strandi Stierlin, 1903 (Anthonomus), syn. n. of Anthonomus (Paranthonomus) varians (Paykull, 1792)variabilis Hoffmann, 1963 (Anthonomus), syn. n. of Anthonomus (Persexarthrus) brevispinus Pic, 1902germanicus Dieckmann, 1968 (Anthonomus (Anthonomidius)), spec. n.morosus Faust, 1891 (Anthonomus (Anthonomidius)), Lectotyperubripes Gyllenhal, 1836 (Anthonomus (Anthonomidius)), Lectotypebituberculatus Thomson, 1868 (Anthonomus (Anthonomus)), Lectotypebrunnipennis Curtis, 1840 (Anthonomus (Anthonomus)), Lectotypechevrolati Desbrochers, 1868 (Anthonomus (Anthonomus)), Lectotypeconspersus Desbrochers, 1868 (Anthonomus (Anthonomus)), Lectotypecurtulus Desbrochers, 1892 (Anthonomus (Anthonomus)), Lectotypegrilati Desbrochers, 1888 (Anthonomus (Anthonomus)), Lectotypekirschi Desbrochers, 1868 (Anthonomus (Anthonomus)), Lectotypekoenigi Pic, 1912 (Anthonomus (Anthonomus)), Lectotypeconnexus Dieckmann, 1968 (Anthonomus (Anthonomus) chevrolati), sspec. n.pubescens (Paykull, 1792) (Anthonomus (Paranthonomus)), Lectotype described as Curculio pubescensbaudueri Desbrochers, 1875 (Anthonomus (Persexarthrus)), Lectotypebrevispinus Pic, 1902 (Anthonomus (Persexarthrus)), Lectotypepineti (Paykull, 1792) (Brachonyx), Lectotype described as Curculio pineticarbonarius Reitter, 1884 (Bradybatus), syn. n. of Bradybatus (Bradybatus) kellneri Bach, 1854inermis Penecke, 1926 (Bradybatus), syn. n. of Bradybatus (Bradybatus) seriesetosus Petri, 1912creutzeri Germar, 1824 (Bradybatus (Bradybatus)), Lectotypekellneri Bach, 1854 (Bradybatus (Bradybatus)), Lectotypetomentosus Desbrochers, 1892 (Bradybatus (Bradybatus)), Lectotypeabeillei Desbrochers, 1888 (Bradybatus (Nothops)), Lectotypegrandoides Dieckmann, 1968 (Bradybatus (Nothops)), spec. n.ornatoides Reitter, 1898 (Bradybatus (Nothops)), syn. n. of Anthonomus (Persexarthus) baudueri Desbrochers, 1875gounellei Pic, 1902 (Macrobrachonyx), Lectotypefunebris Hoffmann, 1963 (Neobradybatus), syn. n. of Anthonomus (Persexarthrus) brevispinus Pic, 1902constrictus Marseul, 1871 (Sphincticraerus), syn. n. of Sphincticraerus lethierryi (Desbrochers, 1869)strangulatus Tournier, 1873 (Sphincticraerus), Lectotype described as Aubeus strangulatus